Water treatment and purification technology - Ryan, W. J. (India : Agrobios, 2009)
The purpose of this book is to make available to engineers, plant managers, students and technical men in general a description, under one cover of the several purification and the other processes that are applied to water.
Chapter 1. The impurities in water -- Chapter 2. Sedimentation and coagulation -- Chapter 3. Filtration -- Chapter 4. The Analysis of water -- Chapter 5. The Lime and soda-ash process -- Chapter 6. Ion Exchangers -- Chapter 7. Boiler Feed- Water treatment general considerations -- Chapter 8. Boiler Feed-water treatment methods used -- Chapter 9. Disinfection of water -- Chapter 10. Tastes and odors -- Chapter 11. Miscellaneous treatments -- Chapter 12. Prevention of corrosion -- Appendix.
Includes index.
Keywords: WATER TREATMENT